Clinical Factors in Trunk Capillary Malformations in the Neonate: When to Suspect Other Associated Malformations? A Case–Control Study - Delgado-Miguel, Carlos; Vicente, Miriam; Serrano-Muñoz, Antonio Jesus; Miguel-Ferrero, Miriam; Diaz, Mercedes; Triana, Paloma; López-Gutiérrez, Juan Carlos (European Journal of Pediatric Surgery, 2020)
Introduction Capillary malformations (CMs) can be sporadic or syndromic, in association with other underlying venous malformation (VM) or lymphatic malformation (LM). The objective of this study is to describe the clinical patterns in the neonate that allow us to differentiate sporadic CMs from those associated with other vascular malformations.Materials and Methods A case–control study was performed in neonates with CM located in the trunk, followed at our institution between 2008 and 2018. The patients were divided into two groups: group A (cases: CM associated with VM or LM) and group B (controls: sporadic CM without associated malformations). Demographic and clinical variables collected in the clinical history were evaluated (color, location, multifocality, bilaterality, position regarding the vascular axis, and involvement of the midline).Results Thirty-eight patients were included (18 cases and 20 controls) without differences in gender and age. In group A, the totality of patients presented CM with uniform color and lateral location (p < 0.001). In this group, bilateral and multifocal involvements were lower than in group B, without significant differences between both groups. The distribution of CMs in group A was always parallel to the vascular axis and the midline was always respected, without observing these characteristics in the group B (p < 0.001).Conclusion The presence of a CM in the trunk of a neonate with uniform color, lateral location, parallel position to the vascular axis, and absence of involvement of the midline should make us suspect other underlying vascular malformations, which should be studied with complementary tests.
Keywords: capillary malformations; vascular malformations; neonates; case–control study